The myth of aortic valve annulus changes in aortic valve disease - Yanren Peng; Huijun Hu; Xiaorong Shu; Yongqing Lin; Weibin Huang; Shuwan Xu; Ruqiong Nie (Frontiers in Cardiovascular Medicine, 2023)
BackgroundThe characteristics of aortic annulus changes in aortic regurgitation (AR) patients are poorly understood, and predictive factors among aortic valve disease are yet to be established.ObjectiveThis study seeks to elucidate the pattern of annular size fluctuations across different cardiac phases in AR patients and to identify predictors for annular enlargement during either systole or diastole in aortic valve diseases.MethodsA retrospective analysis was conducted on 55 patients with severe aortic valve diseases, including 26 patients with aortic stenosis (AS) and 29 with AR, to discern the two groups' contrasting and analogous patterns of annular changes. The patient sample was expanded to 107 to investigate the factors influencing the size of the annulus during different cardiac phases. Based on our findings, patients were then divided into two groups: those with an annulus that is larger during systole (83 patients) and those where the annulus is larger during diastole (24 patients).ResultsTypically, AR patients exhibit a dynamic annulus, with both perimeter and area being largest during mid-systole. These dimensions diminish progressively and then increase again in early diastole, a pattern consistent with observations in AS patients. Among 107 patients, 21% had diastolic enlargement. Systolic measurements would lead to prosthesis undersizing in 17% of these. Male gender and lower systolic annulus minimum relative to body surface area (AnMin index) were predictors of diastolic enlargement, with ROC curve areas of 0.70 and 0.87 for AR and AS, respectively.ConclusionsSystolic measurements are recommended for AR patients. Gender and the AnMin index are significant predictors, particularly potent in AS patients.